2010
DOI: 10.4314/ijhr.v2i2.55402
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month review of medical admissions in a nigerian teaching hospital

Abstract: and full-text of published articles. The journal is devoted to the promotion of health sciences and related disciplines (including medicine, pharmacy, nursing, biotechnology, cell and molecular biology, and related engineering fields). It seeks particularly (but not exclusively) to encourage multidisciplinary research and collaboration among scientists, the industry and the healthcare professionals. It will also provide an international forum for the communication and evaluation of data, methods and findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 2 publications
2
5
2
Order By: Relevance
“…Different from this study is a report from Benin[2] where HIV/AIDS related disorders were the most common cause of mortality (43.5%) followed by endocrine disease principally DM.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Different from this study is a report from Benin[2] where HIV/AIDS related disorders were the most common cause of mortality (43.5%) followed by endocrine disease principally DM.…”
Section: Discussioncontrasting
confidence: 76%
“…Case fatality rates for strokes and HIV/AIDS were the highest (27.9% and 25.2% respectively) hence the need for targeted interventions to combat the menace of these disorders in our communities. Different from this study is a report from Benin[ 2 ] where HIV/AIDS related disorders were the most common cause of mortality (43.5%) followed by endocrine disease principally DM.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Of the 14 studies carried out in university/teaching hospitals nine reported having class III diagnostic facilities (26–28, 30, 42, 43, 47–49). These included more advanced imaging, pathology, and biochemical tests.…”
Section: Resultsmentioning
confidence: 99%